Production of protease from bacillus stearothermophilus F1 - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Abdul Razak, Che Nyonya; Ampon, Kamaruzaman; Mohd Yusoff, Khatijah; Abd Hamid, Suhaili; Fu, Zhibiao (2004)
A biologically pure strain of Bacillus stearothermophilus F1 capable of producing protease which is tolerant to any organic compound selected from the group leucine, cysteine, arginine, glycine, asparagine (BDH) and aspartic acid. Peptone iv derived from soybean was the best organic compound for the enzyme production. Sodium nitrate, ammonium salts and amino acids as sole nitrogen sources interfered with protease formation. In addition Bacteriocin-release-protein (BRP) system was used for the release of heterologous proteins from Escherichia coli into culture medium. The gene from the alkaline protease was cloned from Bacillus stearothermophilus F1 and the recombinant F1 protease was efficiently excreted into the culture medium using two vectors pTrcHis bearing the protease gene and pJL3 containing the BRPs. The recombinant enzyme was purified through single-step heat treatment at 70.degree. C. for 3 hours at pH level from 8 to 10.